IN-VITRO ANTI-ARTHRITIC ACTIVITY OF METHANOLIC EXTRACT OF MOMORDICA CHARANTIA FRUIT - ., Shivali; Singh, Divya; Chaudhary, Suresh Kumar; Arora, Pankaj; Gautam, Rupesh K. (Asian Journal of Pharmaceutical Research and Development, 2024)
The present study was aimed at the investigation of anti-arthritic activity in methanolic extract of M. charantia. The antiarthritic activity of M. charantia Methanolic Fruit Extract was done by inhibition of protein denaturation and human red blood cell membrane stabilization (HRBC) in-vitro methods. The methanolic extract of M. charantia was subjected to invitro inhibition of protein denaturation in various concentrations i.e. 10, 20, 40, 80, 100 and160μg/ml. HRBC method was also used for the estimation of anti-arthritic activity from in various concentrations 10, 20, 40, 80, 100 and 160 μg/ml. In the results M. charantia Methanolic Fruit Extract exhibited a concentration dependent both in-vitro models (inhibition of protein denaturation& stabilization of HRBC membrane) showed a concentration dependent anti-arthritic activity, and the protection percent increased with increase in the concentration of the M. charantia Methanolic Fruit Extract. So, in the conclusion the present study is support to the isolation and use of phytoconstituents from fruit M. charantia in the treatment of arthritis.